2021
DOI: 10.1093/rheumatology/keab507
|View full text |Cite
|
Sign up to set email alerts
|

All-cause and cause-specific mortality in patients with giant cell arteritis: a nationwide, population-based cohort study

Abstract: Objectives To investigate whether giant cell arteritis (GCA) is associated with increased all-cause and cause-specific mortality. Methods A nationwide, population-based cohort study in Denmark using medical and administrative registries. GCA cases were defined as patients aged ≥50 years from 1996-2018 with a first-time discharge diagnosis of GCA and ≥3 prescriptions for prednisolone within 6 months following diagnosis. Each G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Thus, the higher risk of aortic dilation in GCA patients is unanimously admitted today. Other cohort studies confirmed that patients with aortic dilation have an increased mortality, especially secondary to aortic dissections [11][12][13]68,69].…”
Section: Aortic Complications In Gcamentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, the higher risk of aortic dilation in GCA patients is unanimously admitted today. Other cohort studies confirmed that patients with aortic dilation have an increased mortality, especially secondary to aortic dissections [11][12][13]68,69].…”
Section: Aortic Complications In Gcamentioning
confidence: 89%
“…As an inflammatory vascular disease, GCA can be directly and indirectly responsible for cardiovascular (CV) events. Thanks to large-registry studies, it is nowadays wellestablished that GCA is associated with an increased risk of CV events [8][9][10], increasing the mortality from CV origin [11][12][13]. By definition, GCA patients are over 50 and they are even more frequently between 70 and 80 years old, an age at which usual cardiovascular risk factors and atherosclerosis are also common [14].…”
Section: Introductionmentioning
confidence: 99%
“…The GiACTA trial demonstrated the superiority of the combination of tocilizumab and corticosteroids versus placebo and corticosteroids in terms of sustained corticosteroid-free remission but did not report changes in disease-related mortality [3]. Given that GCA mortality is primarily due to glucocorticoid-related complications (e.g., infections, cardiovascular disease, endocrinopathies), it is still reasonable to hypothesize that tocilizumab may reduce GCA mortality by decreased glucocorticoid use over time [26]. In addition, not all patients with GCA receive tocilizumab due to contraindications, physician judgment or patient preference.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Mortality is not increased in PMR, 56 57 whereas in GCA, patients have higher mortality, particularly at disease onset, most likely as a consequence of disease manifestations and adverse effects of intensive treatment. 58 Among disease-related symptoms, patients pay particular attention to pain, stiffness, disability and fatigue. 48 59 In GCA, preservation of sight and integrity of other tissues potentially affected by vascular compromise are other fundamental aspects of maintaining a high quality of life.…”
Section: Recommendationmentioning
confidence: 99%